The Global ecology handbook what you can do about the environmental crisis - Corson, Walter Harris; Global Tomorrow Coalition (Boston Beacon Press, 1990)
A comprehensive, easy-to-use, and practical guide on the environment and the linkages among economic development, energy policy, population growth, and other issues as well as what we can do in our daily life to help solve today's environmental problems and improve the quality of life for everyone. Includes chapters on tropical rain forests, the garbage glut, oceans and coasts, global warming, population growth, agriculture, biological diversity, fresh water, hazardous waste, environment and development.
A global awakening -- Foresight capability -- Population growth -- Development and the environment -- Food and agriculture -- Biological diversity -- Tropical forests -- Ocean and coastal resources -- Fresh water -- Nonfuel minerals -- Energy -- Air, atmosphere, and climate -- Hazardous substances -- Solid waste management -- Global security -- Toward a sustainable future -- What you can do.
"Practical supplement to the PBS series, Race to save the planet."
Includes bibliographical references (p. 351-398).
Keywords: Environmental protection -- Citizen participation